Extended-Spectrum β-Lactamase and Carbapenemase Producing Gram-Negative Bacilli Infections Among Patients in Intensive Care Units of Felegehiwot Referral Hospital: A Prospective Cross-Sectional Study - Alebel M; Mekonnen F; Mulu W (Infection and Drug Resistance, 2021)
Mekonnen Alebel,1 Feleke Mekonnen,2 Wondemagegn Mulu2 1Department of Clinical Laboratory Science, Chagni Hospital, Chagni, Ethiopia; 2Department of Medical Laboratory Science, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, EthiopiaCorrespondence: Wondemagegn MuluDepartment of Medical Laboratory Science, College of Medicine and Health Sciences, Bahir Dar University, P. O. Box: 79, Bahir Dar, EthiopiaEmail wondem_32@yahoo.comBackground: Owing to the specific risk profile of its residents, intensive care units (ICUs) are the best place for selection pressure and the epicenter for resistance development and dissemination. Infections with β-lactamase releasing Gram-negative bacilli (GNB) at ICUs are an emerging global threat. This study dogged the magnitude of extended-spectrum β-lactamase (ESBL) and carbapenemase releasing Gram-negative bacilli infections and associated factors among patients in the ICUs of Felegehiwot Referral Hospital, Ethiopia.Methods: A cross-sectional study was done through February to June 2020. Wound swabs, urine, blood and sputum samples were collected from patients in the ICUs symptomatic for infections while excluding those under coma and shock. Bacterial species were verified using standard microbiological methods. Carbapenemase and ESBL production were identified using modified carbapenem inactivation and combined disk diffusion methods, respectively. Multivariable analysis was calculated for factors associated with ESBL production. P-value < 0.05 was taken as cut-off for statistical significance.Results: Out of 270 patients in the ICU, 67 (24.8%) and 14 (5.2%) had infections with ESBL and carbapenemase releasing GNB, respectively. The most frequent ESBL producing isolates were P. aeruginosa (100%), E. cloacae (100%), K. pneumoniae (82.8%) and E. coli (64%). The predominant carbapenemase producer isolates were K. pneumoniae (27.6%) and E. cloacae (33.3%). Overall, 77 (81.1%) of species were multi-drug resistant. All GNB species were 100% resistant to tetracycline and ampicillin. They are also resistant to cefuroxime, ceftazidime, sulfamethoxazole-trimethoprim and cefotaxime. Prior hospitalization (AOR = 5.5, CI = 2.63– 11.46), support with medical care devices (AOR = 23.7, CI = 4.6– 12) and arterial intravenous catheterization (AOR = 2.7, CI = 1.3– 5.3) had significant association with β-lactamase producing GNB infection.Conclusion: Infection with ESBL and carbapenemase producing Gram-negative bacilli linked with an alarming degree of multi-drug resistant isolates is a major healthcare threat among patients in ICUs. Hence, strict adherence to infection prevention practices and wise use of antibiotics are recommended to slow the spread of antimicrobial resistance.Keywords: ICU, GNB, ESBL, carbapenemase, multi-drug resistance, FHRH, Ethiopia